Karakteristik Ekstrak Pewarna Alami Buah Naga Merah (Hylocereus Polyrhizus) dengan Variasi Rasio Pelarut dan Asam - Anisa Aprilia; Andi Eko Wiyono; Andrew Setiawan Rusdianto (Jurnal Teknologi dan Industri Pertanian Indonesia, 2025)
Dyes are materials that people use for certain purposes. However, the high use of synthetic dyes in non-food products causes environmental pollution and is toxic. Therefore it is necessary to provide another alternative in the form of natural dyes from plants, namely red dragon fruit. This fruit contains anthocyanin as a red dye. Natural dyes are obtained through an extraction process with the same solvent as their properties, such as ethanol. The choice of ethanol to be used as a solvent is usually added with acid to stabilize and optimize the extracted pigments, one of which is citric acid. This combination is useful for dissolving substances that dissolve in polar solvents such as anthocyanins. The aim of the study was to determine the effect of varying solvent and acid ratios on the physical and chemical characteristics of red dragon fruit-based natural dye extracts and to determine the best variation of solvent and acid ratios in red dragon fruit-based natural dye extracts. Data analysis used a single factor Completely Randomized Design (RAL), namely variations in the ratio of solvent and acid. The results of this study stated that variations in the ratio of solvent and acid had a significant effect on the overall characteristics of the red dragon fruit natural dye extract. Selection of the best treatment using the effectiveness index method was obtained in treatment D with a pH of 2.3; yield 24%; total dissolved solids 50.08 oBrix; color value a 27.44 and anthocyanin content 70.18 mg/100 mL.